Speaking clearly? The mediation role of leader pro-voice behavior and LMX on the relationship between paradoxical leadership and individual creativity - Silva, V. H.; Duarte, A.P.; Simões, L. M. (22nd European Congress of Work and Organizational Psychology, 2025)
Currently, organizations operate in a world characterized by volatility, uncertainty, complexity, and ambiguity. This environment, often described as challenging and dynamic, demands leaders capable of managing paradoxes and navigating challenging demands. Paradoxical leadership has emerged as a strategy to address these challenges. This approach refers to a leader's ability to balance seemingly contradictory behaviors to meet opposing workplace demands simultaneously and over time. However, to adapt to the needs of this unpredictable world, organizations must foster creativity, both at the organizational level and among individual employees, to implement changes that align with constant instability. Despite its potential, research indicates that paradoxical leadership does not always directly promote creativity to the desired extent. This suggests there are other underlying psychosocial variables that may influence the relationship between paradoxical leadership and creative outcomes. To explore this relationship, the current study, specifically, focuses on the role of leader pro-voice behavior, the extent to which leaders encourage employees to express ideas, and leader-member exchange, which reflects the quality of the relationship between paradoxical leaders and their subordinates creativity. The study employed a time-lagged correlational design with a two-week interval. Data were collected from 151 employees from diZerent organizations. In the first phase, participants answered scales related to paradoxical leadership, leader pro-voice behavior, and leader-member exchange. In the second phase, data on individual creativity was gathered. All measures revealed high reliability. The sequential mediation model was tested using Process for SPSS, Model 6. The results revealed that the connection between paradoxical leadership and individual creativity is mediated sequentially by leader pro-voice behavior and leader-member exchange. This study contributes to existing literature by clarifying the mechanisms through which paradoxical leadership enhances individual creativity. It emphasizes the importance of fostering open communication and building strong leader-employee relationships to unlock innovation.